Finite-time adaptive synchronization of fractional-order delayed quaternion-valued fuzzy neural networks - Chen, Shenglong; Li, Hong-Li; Wang, Leimin; Hu, Cheng; Jiang, Haijun; Li, Zhiming (Nonlinear Analysis: Modelling and Control, 2023)
Based on direct quaternion method, this paper explores the finite-time adaptive synchronization (FAS) of fractional-order delayed quaternion-valued fuzzy neural networks (FODQVFNNs). Firstly, a useful fractional differential inequality is created, which offers an effective way to investigate FAS. Then two novel quaternion-valued adaptive control strategies are designed. By means of our newly proposed inequality, the basic knowledge about fractional calculus, reduction to absurdity as well as several inequality techniques of quaternion and fuzzy logic, several sufficient FAS criteria are derived for FODQVFNNs. Moreover, the settling time of FAS is estimated, which is in connection with the order and initial values of considered systems as well as the controller parameters. Ultimately, the validity of obtained FAS criteria is corroborated by numerical simulations.
Keywords: quaternion-valued fuzzy neural networks; fractional order; finite-time synchronization; adaptive control; time delay